Dance of the furies : Europe and the outbreak of World War I - Neiberg, Michael S. (The Belknap Press of Harvard University Press, 2011)
"Neiberg marshals letters, diaries, and memoirs of ordinary citizens across Europe to show that the onset of war was experienced as a sudden, unexpected event. As they watched a minor diplomatic crisis erupt into a continental bloodbath, they expressed shock, revulsion, and fear. But when bargains between belligerent governments began to crumble under the weight of conflict, public disillusionment soon followed. Yet it was only after the fighting acquired its own horrible momentum that national hatreds emerged under the pressure of mutually escalating threats, wartime atrocities, and intense government propaganda"--Jacket